(untitled) (Alternautas, 2022)
This article looks at the archaeological heritage along the rapids of the Tapajós River and its tributaries, such as the Juruena and Teles Pires Rivers, based on the existing record. Apart from archaeology, historical sources as well as oral history may also shed some light on the (often turbulent) past of the Tapajós Valley after the Portuguese conquest (Menéndez, 1981/1982, 2006 [1992]). They also point at the possible location of archaeological sites; stemming from the review of historical and archaeological sources, Alexandre Robazzini (2013) has compiled a comprehensive table containing 423 archaeological sites in the Tapajós Valley. Notwithstanding the limited amount of archaeological fieldwork carried out in the region where the government intends to build the Tapajós Hydroelectric Complex (CHT) –and in contrast to the idea promoted by the official discourse that the area in question is empty and has no history- we present some evidence here that points to the richness and singularity of the existing archaeological heritage. Far from being located in a virgin forest, the Tapajós and its tributaries irrigate an area that has been anthropized, or in other words, altered by humans for thousands of years.